Cover Feature: Alloy‐Mediated Ultra‐Low CO Selectivity for Steam Reforming over Cu−Ni Bimetallic Catalysts (ChemCatChem 18/2018). Issue 18 (21st September 2018) - Ma, Kui; Cui, Zhonghui; Zhang, Zhitao; Huang, Jingjing; Sun, Zhirui; Tian, Ye; Ding, Tong; Li, Xingang
Abstract : The Cover Feature illustrates an efficient dimethyl ether/methanol steam reforming process to produce highly purified hydrogen with ultra‐low CO selectivity over a Cu−Ni bimetallic catalytic system. In their Full Paper, K. Ma et al. introduce an in situ approach for the tunable synthesis of Cu−Ni alloys which are used as bimetallic catalysts, and exhibit an alloy‐mediated selectivity to CO for the steam reforming reaction. The Cu−Ni alloy absorbs CO strongly at high temperatures, as verified by in situ DRIFTS, which results in the ultra‐low CO production in hydrogen‐rich reformates. This work opens a new avenue for design of commercial reforming systems for on‐board fuel cells. More information can be found in the Full Paper by K. Ma et al. onpage 4010 in Issue 18, 2018 (DOI:10.1002/cctc.201800684 ).